Foraging Variation of Bombus species with Plant Families and Floral Colors in Chitwan Annapurna Landscape, Nepal - Ghimire, Kishor Chandra; Pandey, Anjeela; Joshi, Ganesh Datt; Bhusal, Daya Ram (Journal of Institute of Science and Technology, 2022)
Little is known about the effect of the type of vegetation and floral color on the foraging behavior of Bombus species. In this work, we have investigated the differential foraging association of bumblebees (Bombus spp.) with the specific flower color and the plant families in Chitwan-Annapurna Landscape (CHAL). The specimens were collected between April to October 2019 and field visits were carried out by following accessible walking transects between 600 to 3500 m asl covering different habitats of the study area. The bumblebees were collected by opportunistic methods using a sweeping net. We found that the relative frequency of Bombus spp. varied significantly with the families of local flowering plants and the particular colors of flowers. Some of the bumblebees visited at the specific plant family for nectar and pollen indicating the specific association with particular flower morphology and color. This study, therefore, gives an insight into the differential foraging preference of Bombus spp. to certain plant families with selected specific colors in CHAL.